(untitled) (Nexo Revista Científica, 2022)
The introduction of such plasticizers as tributyl phosphate and di-(2-Ethylhexyl)-sebacate [DEHS] into the composition of polyurethane elastomers, synthesized through the stage of epoxyurethane oligomer can significantly reduce the glass transition temperature, which expands the operating temperature range. The peculiarities of changes in the basic properties of the studied elastomers during plasticization are determined by their two-phase structure, which is characterized by hard urethane hydroxyl blocks.